Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Combined membrane aeration and membrane filtration for space-efficient nitrogen control in reuse-oriented biological pretreatment - Hsin-Chieh Lin; Ting-Wei Wu; Yu-Tzu Huang; Ho Kyong Shon; Chia-Hung Hou (Desalination, 2026)

Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Integrated multi-matrix bile acid metabolic metrics (BAMMs): A methodological framework for functional metabolic phenotyping in human subjects - Cheng-Hung Yang; Hsiang-Yu Tang; Chun-Ming Fan; Jui-Fen Lin; Mei-Ling Cheng (Analytica Chimica Acta, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Enhanced label-free SERS detection of uremic toxins in clinical spent dialysate - Han Lee; Jiunn-Der Liao; Yi-Shan Guo; Chung-Yu Wang; Kuan-Hung Liu; Szu-Hsueh Lai; Bo-Shen Lin (Analytica Chimica Acta, 2026)

Microbial-derived metabolites coordinate growth regulation and stress tolerance in Phalaenopsis orchids - Nur Izzatul Maulidah; I-Hung Lin; Yun-Teng Yen; Ting-Yu Liou; Huey-wen Chuang (Journal of Plant Physiology, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Efficient Underwater Image Super-Resolution via Learnable Color Conversion and Dual-Branch Mamba Network - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh; Yi-Shiuan Yang; Chua-Chin Wang (Journal of Marine Science and Engineering, 2026)
Underwater image super-resolution plays an important role in marine exploration, as it aims to recover clearer and higher-resolution images from degraded low-resolution observations. However, in underwater environments, this task is particularly challenging due to non-uniform spectral attenuation and particle scattering. Underwater, red light fades quickly, leading to color distortion and loss of details. To address this while keeping the model lightweight, we propose a dynamic color-space network for single-image super-resolution. Traditional methods use fixed color conversion and cannot handle non-uniform attenuation well. We instead use a learnable module to adaptively obtain luminance (Y) and chrominance (CbCr) representations. Building upon this representation, we employ a highly efficient dual-branch architecture where the Y-channel features are processed using light Mamba blocks to capture spatial dependencies with linear complexity, while the CbCr-channel features are restored by a lightweight convolutional neural network. Finally, a lightweight residual model utilizing depth-wise separable convolutions (DSC), deformable convolutions, and pixel attention mechanisms is introduced to refine the features and suppress artifacts. Experimental results demonstrate that while achieving competitive restoration quality, the proposed method drastically reduces computational complexity and parameter count compared to other large-scale models. This balance between visual quality and computational efficiency makes the proposed method well-suited for real-time deployment on resource-constrained autonomous underwater vehicles (AUVs).

Short-term exposure to nitrogen dioxide and risk of stroke-related re-admission: An analysis of the Taiwan National Health Insurance Research Database - Chen-Ting Yang; Yu-hsiang Lin; Hung-Lin Lin; Der-Cherng Chen; Chun-Chung Chen; Der-Yang Cho (Atmospheric Environment, 2026)

Purification, Identification, and Functional Validation of Anti-Inflammatory Peptides from Protein Hydrolysates of Asian Seabass, Lates Calcarifer by-Product - Hui-Chen Lin; Chung-Chih Tseng; Jia-Yu Lu; Hua-Yi Liang; Chun-Hung Liu (Marine Biotechnology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Effect of somatosensory games on arterial stiffness and antioxidant status in postmenopausal women - Yi-Hung Liao; Kunanya Masodsai; Yu-Chi Kuo; Hsiao-Kuan Wu; Yi-Yuan Lin (European Journal of Applied Physiology, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Triarylamine-based epoxy thermosets featuring bright polyelectrochromic energy-storage and energy-saving behaviors - Yu-Jen Shao; Peng-Yi Lin; Hung-Lin Ho; Hsuan-Hsi Pai; William Sun; Yu-Jie Wang; Cha-Wen Chang; Guey-Sheng Liou (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Effects of dietary selenium supplementation on physiological parameters, tissue fatty acid composition, and fatty acid-metabolism relative gene expression of grouper (Epinephelus coioides) fed high plant protein diets - Yen-Chun Lee; Ying-Chieh Lin; Yu-Sheng Huang; Yu-Hung Lin (Fish Physiology and Biochemistry, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Outdoor-like running indoors: an enhanced adaptive treadmill with real-time physiological monitoring - Pei-Chun Hung; Yu-Chen Liu; Chun-Liang Lin; Wu-Chung Su; Chian-Yu Lu (Next Research, 2025)

Predictions about the hourly effluents in the real anaerobic-oxic wastewater treatment process made by the optimized bidirectional long short-term memory network - Yu-Hao Lin; Hung-Hsiao Hsu; Ping-Yu Liu (Journal of Water Process Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Sustainable energy generation through engineered copper molybdate: a ternary metal oxide catalyst for efficient oxygen evolution in alkaline environments - Hung-Chang Cheng; Dhanapal Vasu; Hsin-Yu Lin; Zhen-Yuan Lan; Leggins Abraham; Tetsu Yonezawa; Te-Wei Chiu (Fuel, 2025)

Biocontrol potential and cryopreservation of marine ciliates for sustainable management of bacterial pathogens in aquaculture - Xin-Long Liu; Sin-Wei Lin; Wei-Yu Yeh; Hung-Yun Lin; Han-Jia Lin (Fish & Shellfish Immunology, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Influence of Human Activity on Wet Deposition and Nitrogen Species in Coastal and Marine Environments - Hung-Yu Chen; Jia-Han Lin; FuJung Tsai (Journal of Marine Science and Engineering, 2025)
In this study, 101 and 102 rainwater samples were collected from April 2020 to February 2024 in a coastal and marine area, respectively. The results show that the Cl/Na ratios in both study areas were lower than the seawater value (1.17), suggesting chloride depletion. The chloride depletion rates in both areas decreased after the COVID-19 lockdown period. The molar ratio of NH4+ to non-sea-salt sulfate (nss-SO42−) was 1.54, with a mixture of (NH4)2SO4 and NH4HSO4 in the coastal area, and 0.83, with NH4HSO4 as the main form, in the marine area. A decreasing trend attributed to high O3 and relative humidity (RH) levels occurred in 2022. Among the dissolved organic nitrogen (DON) species, DON accounted for 24% and 32% of the total dissolved nitrogen (TDN) in the coastal and marine areas, respectively, indicating a greater relative contribution under lower anthropogenic influence. On the basis of the correlation between the species and source analysis results, NO3− mainly originated from fossil fuel combustion, NH4+ originated from agricultural emissions and secondary aerosols, and DON originated from secondary aerosols via combustion processes and natural emissions. In terms of the flux, due to lockdown activities, the Dissolved Inorganic Nitrogen (DIN) flux decreased significantly from 40.6 to 19.3 mmol m−2 yr−1 in the coastal area and from 27.7 to 15.1 mmol m−2 yr−1 in the marine area. Additionally, a slight decrease occurred in the DON flux, from 21.6 to 19.3 mmol m−2 yr−1 and from 27.7 to 15.1 mmol m−2 yr−1, respectively. Regarding new production, based on nitrogen input, the level in the coastal area decreased from 5.83 to 2.10 g C m−2 yr−1, and that in the marine area decreased from 3.92 to 1.55 g C m−2 yr−1, indicating a significant reduction during the COVID-19 lockdown.

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Effective peroxymonosulfate activation over cobalt oxide (CoO)/nitrogen-doped graphene aerogel for rhodamine b degradation - Xian-Lun Liao; Dhayanantha Prabu Jaihindh; Tzu-Ting Chang; Yi-Feng Lin; Wei-Hung Chiang; Yu-Chun Wang (Journal of Water Process Engineering, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Effects of l-carnitine supplementation in diet on growth, lipid metabolism, and carnitine biosynthesis in juvenile giant grouper (Epinephelus lanceolatus) fed high plant protein diets - Yu-Hung Lin; Yen-Chun Lee; Chih-Chieh Yeh (Aquaculture, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Perhydroxylated benzoquinoid covalent triazine framework for ultra-high-density lithium-ion storage - Nhu T.H. Luu; Rajeshkumar Anbazhagan; Alexander S. Ivanov; Sung-En Lin; Chia-Hsin Chang; Chen-Yu Hung; Ilja Popovs; Jui-Chin Lee; Teng-Hao Chen; Watchareeya Kaveevivitchai (Chemical Engineering Journal, 2025)

Canagliflozin-driven cellular re-differentiation and migration inhibition in vascular smooth muscle cells via PTEN upregulation - Ming-Jer Hsieh; Dong-Yi Chen; Cheng-Hung Lee; Yu-Cih Liao; Miao‐Sui Lin; Jong-Hwei S. Pang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Fate and health implications of polycyclic aromatic hydrocarbons in a sustainable food waste recycling system using housefly maggots and Nile tilapia - Chao Zheng; Zhang Cheng; Zhi-Lin Chen; Yu Bon Man; Qiao Liu; Liu-Lan Zhao; Song Yang; Ming Hung Wong (Aquaculture, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Methane dynamics controlled by subsurface metabolic architecture and tidal cycling in a mangrove wetland - Tzu-Hsuan Tu; Tai-Yi Lee; Zih-Huei Yu; Chun-Hung Lu; Yueh-Ting Lin; Pei-Ling Wang (Science of The Total Environment, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

SYNLAC Prime probiotics alleviate Enterocytozoon hepatopenaei-induced damage in white shrimp, Penaeus vannamei by enhancing growth, immunity, and resistance to Vibrio parahaemolyticus - Ann-Chang Cheng; Hsiao-Tung Chang; Ting-Yu Lee; Jin-Seng Lin; Chun-Hung Liu (Fish & Shellfish Immunology, 2025)

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

High sensitivity mercury ion detection via thermal shock and quench with molecular sieve-functionalized FETs - Guan-Cheng Zeng; Hsuan-Wei Huang; Chia-Kai Lin; Jung-Chih Chen; Sheng-Chun Hung; Guo-Chun Dong; Yu-Lin Wang (Chemical Engineering Journal, 2025)

The influence of shading facilities on outdoor thermal comfort, pedestrian walking speed, and indoor satisfaction - Zi-En Lin; Shiang-Yu Wang; Kuo-An Hung; Chiao-Jou Hsieh; Tzu-Ping Lin (International Journal of Biometeorology, 2025)

Microplastic contamination in the gastrointestinal tracts of larval fish assemblages from coastal waters in southwestern Taiwan - Ming-Yih Leu; Sun-Hon Lin; Te-Yu Chen; Fung-Chi Ko; Shao-Hung Peng (Regional Studies in Marine Science, 2025)

Investigating the Sensitivity of NIPAM Gel Dosimetry in CyberKnife Systems Using MRI-based R2 Mapping - Yu-Hsuan Lin; Shih-Wei Huang; Hung-Yi Chen; Hao-Ting Lan; Feng-Yi Su; Shin-Lei Peng; Chun-Hsu Yao (Journal of Medical and Biological Engineering, 2025)
Purpose The CyberKnife delivers precise radiation with sharp dose gradients challenging to measure. N-isopropylacrylamide (NIPAM) gel phantom can capture 3D dose distributions effectively. This study investigates the feasibility of using NIPAM gel dosimetry combined with magnetic resonance imaging (MRI)-based transverse relaxation rate (R2) mapping to verify dose distributions delivered by the CyberKnife system. Methods A total of 24 gel samples were divided into 8 dose groups (0, 3, 6, 9, 12, 15, 18, and 21 Gy), with three samples per dose group for repeat measurements. The NIPAM polymer gels were irradiated by a CyberKnife ® M6 FIM system with a 6 MV x-ray beam. MR images of the NIPAM gel phantom were made 24 h after irradiation using the 3T MRI scanner. The R2 maps corresponding to dose distribution were analyzed using Matlab software. Results Our results demonstrate that R2 values increase with rising irradiation doses, confirming dose-dependent sensitivity. The dose-response curve exhibits a slope of 0.1688 Gy⁻¹ s⁻¹, reflecting the gel dosimeter’s sensitivity, with a strong correlation (R² = 0.85, p = 0.001). Additionally, R2 values vary with depth, peaking at the 30 mm dose center point (D center ) and then gradually decreasing, indicating maximum dose accumulation at D center followed by a decline with increasing depth. Conclusion This study demonstrates that NIPAM gel dosimetry with MRI-based R2 mapping effectively verifies CyberKnife dose distributions. It exhibits strong dose sensitivity and accurately captures sharp gradients, highlighting its potential as a superior alternative to conventional dosimetry methods.

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Indoxyl Sulfate Induces Ventricular Arrhythmias Attenuated by Secretoneurin in Right Ventricular Outflow Tract Cardiomyocytes - Yuan Hung; Chen-Chuan Cheng; Yen-Yu Lu; Shih-Yu Huang; Yao-Chang Chen; Fong-Jhih Lin; Wei-Shiang Lin; Yu-Hsun Kao; Yung-Kuo Lin; Shih-Ann Chen; Yi-Jen Chen (Cardiovascular Toxicology, 2025)

High performance catalyst CoNP for efficient electrochemical production of hydrogen peroxide - Ko-Shan Ho; Kuan-Ying Hung; Yu-Lin Hsiao; Hsiu-Chung Tu (Journal of Environmental Chemical Engineering, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Optimizing sediment control by adjusting the relative spacing between trusses/beams in an open-type check dam - Hung-En Chen; Tzu-Yu Chen; Ya-Lin Zheng; Yen-Yu Chiu; Su-Chin Chen (Landslides, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Dual-CycleGANs with Dynamic Guidance for Robust Underwater Image Restoration - Yu-Yang Lin; Wan-Jen Huang; Chia-Hung Yeh (Journal of Marine Science and Engineering, 2025)
The field of underwater image processing has gained significant attention recently, offering great potential for enhanced exploration of underwater environments, including applications such as underwater terrain scanning and autonomous underwater vehicles. However, underwater images frequently face challenges such as light attenuation, color distortion, and noise introduced by artificial light sources. These degradations not only affect image quality but also hinder the effectiveness of related application tasks. To address these issues, this paper presents a novel deep network model for single under-water image restoration. Our model does not rely on paired training images and incorporates two cycle-consistent generative adversarial network (CycleGAN) structures, forming a dual-CycleGAN architecture. This enables the simultaneous conversion of an underwater image to its in-air (atmospheric) counterpart while learning a light field image to guide the underwater image towards its in-air version. Experimental results indicate that the proposed method provides superior (or at least comparable) image restoration performance, both in terms of quantitative measures and visual quality, when compared to existing state-of-the-art techniques. Our model significantly reduces computational complexity, resulting in a more efficient approach that maintains superior restoration capabilities, ensuring faster processing times and lower memory usage, making it highly suitable for real-world applications.

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

SYNLAC prime probiotics enhances growth performance, and resistance of white shrimp, Penaeus vannamei to Enterocytozoon hepatopenaei and Vibrio alginollyticus: Insights into immune and metabolic pathway modulations - Ann-Chang Cheng; Hsiao-Tung Chang; Ting-Yu Lee; Jin-Seng Lin; Chun-Hung Liu (Fish & Shellfish Immunology, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Targeting PADI2 as a potential therapeutic strategy against metastasis in oral cancer via suppressing EMT-mediated migration and invasion and CCL3/5-induced angiogenesis - Shih-Kai Hung; Chih-Chia Yu; Hon-Yi Lin; Wen-Yen Chiou; Moon-Sing Lee; Ru-Inn Lin; Ming-Chi Lu (Clinical & Experimental Metastasis, 2024)

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Systematic establishment of the relationship between skin absorption and toxicity of furanoids via in silico, in vitro, and in vivo assessments - Yin-Ku Lin; Chien-Yu Hsiao; Chih-Jung Chen; Ahmed Alalaiwe; Chin Lee; Tse-Hung Huang; Jia-You Fang (Environmental Research, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

Soluble Epoxide Hydrolase Inhibitor Ameliorates Olfactory Dysfunction, Modulates Microglia Polarization, and Attenuates Neuroinflammation after Ischemic Brain Injury - Chien-Fu Yeh; Tung-Yueh Chuang; Ming-Ying Lan; Yung-Yang Lin; Wei-Hao Huang; Yu-Wen Hung (Journal of Neuroimmune Pharmacology, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Synergistic Triple-Action morphological composite Anode: Integrating lattice Softening, Interfacial electric Fields, and dual confinement for superior Potassium-Ion battery performance - Jia-Sheng Lin; Yi-Yen Hsieh; Kai-Yuan Hsiao; Yi-Chun Yang; Che-Hung Wang; Ming-Yen Lu; Wen-Wei Wu; Hsing-Yu Tuan (Chemical Engineering Journal, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Elevated surface ozone concentration caused by subtropical cyclones and topographical effect: Model simulation and field measurement - Kuo-Cheng Lo; Wen-Hsi Cheng; Chitsan Lin; Chung-Hsuang Hung; Chung-Shin Yuan; Yu-Lun Tseng (Urban Climate, 2024)

Underwater Image Enhancement Based on Light Field-Guided Rendering Network - Chia-Hung Yeh; Yu-Wei Lai; Yu-Yang Lin; Mei-Juan Chen; Chua-Chin Wang (Journal of Marine Science and Engineering, 2024)
Underwater images often encounter challenges such as attenuation, color distortion, and noise caused by artificial lighting sources. These imperfections not only degrade image quality but also impose constraints on related application tasks. Improving underwater image quality is crucial for underwater activities. However, obtaining clear underwater images has been a challenge, because scattering and blur hinder the rendering of true underwater colors, affecting the accuracy of underwater exploration. Therefore, this paper proposes a new deep network model for single underwater image enhancement. More specifically, our framework includes a light field module (LFM) and sketch module, aiming at the generation of a light field map of the target image for improving the color representation and preserving the details of the original image by providing contour information. The restored underwater image is gradually enhanced, guided by the light field map. The experimental results show the better image restoration effectiveness, both quantitatively and qualitatively, of the proposed method with a lower (or comparable) computing cost, compared with the state-of-the-art approaches.

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Association among polydisperse aerodynamic size of bioaerosols, biodiversity and urbanization in kindergartens - Tzu-Hsien Lin; Ying-Hsiang Chou; Tzu-Yu Hsu; Chun-Hui Hung; Chane-Yu Lai (Chemosphere, 2024)

The removal and transformation of fipronil using a photoelectrochemical device combined with a carbonized TiO2 nanocomposite electrode - Jheng-Sian Yang; Jhen-Cih Wu; Chia-Hung Hou; Angela Yu-Chen Lin (Journal of Water Process Engineering, 2024)

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Heteronemin promotes iron-dependent cell death in pancreatic cancer - Gizem Kaftan; Mümin Alper Erdoğan; Mohamed El-Shazly; Mei-Chin Lu; Shou-Ping Shih; Hung-Yu Lin; Luciano Saso; Güliz Armagan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Overdose with the anesthetic propofol causes hematological cytotoxicity and immune cell alteration in an experimental ex vivo whole blood culture model - Chung-Hsi Hsing; Yu-Ping Hung; Ming-Chung Lin; Chia-Ling Chen; Yung-Ting Wang; Po-Chun Tseng; Rahmat Dani Satria; Chiou-Feng Lin (Toxicology in Vitro, 2024)

Significant changes in cloud radiative effects over Southwestern United States during the COVID-19 flight reduction period - Jingyu Wang; Yun Lin; Xianfeng Wang; Yu Gu; Steve Hung-Lam Yim (Science of The Total Environment, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Breaking prolonged sitting increases 24-h physical activity and self-perceived energy levels but does not acutely affect cognition in healthy adults - Feng-Chih Kuo; Yun-Ting Lin; Ting-Yu Chueh; Yu-Kai Chang; Tsung-Min Hung; Yung-Chih Chen (European Journal of Applied Physiology, 2024)

A numerical investigation of an indoor dry storage facility on heat transfer - Chia-Wei Lin; Yung-Shin Tseng; Kai-Qi Lin; Yu-Hsuan Chang; Tzu-Chen Hung; Hua-Yi Hsu (Annals of Nuclear Energy, 2024)

Exploring the potential of the nano-based sunscreens and antioxidants for preventing and treating skin photoaging - Chih-Hung Lin; Ming-Hsien Lin; Yu-Kuo Chung; Ahmed Alalaiwe; Chi-Feng Hung; Jia-You Fang (Chemosphere, 2024)

Anti-liquefaction mechanisms in buildings with shallow foundations with a focus on lowering the ground water table - Chih-Chieh Lu; Kuan-Yu Chen; Lin-Mao Hu; Wen-Yi Hung (Soil Dynamics and Earthquake Engineering, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Effects of vitamin D and zinc deficiency in acute and long COVID syndrome - Kuang-Yu Chen; Chin-Kuo Lin; Ning-Hung Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

Long-term field calibration of low-cost metal oxide VOC sensor: Meteorological and interference gas effects - Gung-Hwa Hong; Thi-Cuc Le; Guan-Yu Lin; Hung-Wen Cheng; Jhih-Yuan Yu; Racha Dejchanchaiwong; Perapong Tekasakul; Chuen-Jinn Tsai (Atmospheric Environment, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Enhanced biomethane production with a low carbon footprint via anaerobic co-digestion of swine wastewater with rice husk - Hung-Cheng Lin; Shu-Yuan Pan; Yu-I Lin; Dan-Thanh Ngoc Cao (Science of The Total Environment, 2023)

Application of water-saving irrigation and biostimulants on the agronomic performance of maize (Zea mays) - Cheng-Hsuan Chen; Kuan-Hung Lin; Yu-Sen Chang; Yu-Jie Chang (Process Safety and Environmental Protection, 2023)

Estimating the daily average concentration variations of PCDD/Fs in Taiwan using a novel Geo-AI based ensemble mixed spatial model - Chin-Yu Hsu; Tien-Wei Lin; Jennieveive B. Babaan; Aji Kusumaning Asri; Pei-Yi Wong; Kai-Hsien Chi; Tuan Hung Ngo; Yu-Hsuan Yang; Wen-Chi Pan; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Sublethal effects of methylmercury on lateral line sensory and ion-regulatory functions in zebrafish embryos - Giun-Yi Hung; Yu-Chin Pan; Jiun-Lin Horng; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Applying an air curtain to reduce surgical smoke concentration - Xuan-Huy Ninh; Hung-Yu Tzeng; Tak-Wah Wong; Yu-Ting Wu; Yao-Lung Kuo; Ming-Yeng Lin (Air Quality, Atmosphere & Health, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

A novel framework for spatiotemporal groundwater pumping process estimation based on data-driven approaches - Hwa-Lung Yu; Hua-Ting Tseng; Ying-Fan Lin; Chun-Hung Chen; Ying-Chang Kuo; Yun-Ta Cheng (Journal of Hydrology, 2023)

Dietary administration of a postbiotic, heat-killed Pediococcus pentosaceus PP4012 enhances growth performance, immune response and modulates intestinal microbiota of white shrimp, Penaeus vannamei - Rolissa Ballantyne; Jai-Wei Lee; Sz-Tsan Wang; Jin-Seng Lin; Deng-Yu Tseng; Yi-Chu Liao; Hsiao-Tung Chang; Ting-Yu Lee; Chun-Hung Liu (Fish & Shellfish Immunology, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities - Pei-Sheng Chiu; Shine-Wei Ho; Cheng-Hsuan Huang; Yen-Chun Lee; Yu-Hung Lin (Fishes, 2023)
White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022 to 95,858 eggs per spawning event. Hatching occurred approximately 81 h and 26 min after fertilization at a temperature of 27.0 ± 0.9 °C. Newly hatched larvae had a total length (TL) of 1.91–2.03 mm with 24–26 somites. The larvae transformed into juveniles at 30 days post-hatch. Experiments were conducted at different temperatures (21, 24, 27, 30, and 33 °C) and salinities (18, 24, 30, and 36 ppt) to determine the optimal conditions for larval survival and viability. The results indicate that the most suitable conditions in terms of temperature were in the range of 21–27 °C and 30 ppt for salinity. These findings provide valuable insights for the future development of captive-breeding techniques and the commercial production of other marine ornamental gobies.

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Influence of microclimate control on the growth of asparagus under greenhouse in tropical climates - Kuo-An Hung; Yi-Wei Hsu; Yu-Cheng Chen; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Dietary α-tocopherol acetate improved growth performance, lipid oxidative status, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Isabella Ebi; Annita Seok Kian Yong; Leong-Seng Lim; Yu Hung Lin; Rossita Shapawi (Fisheries Science, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

Cadmium exposure induces histological damage and cytotoxicity in the cardiovascular system of mice - Shing-Hsien Chou; Hung-Chen Lin; Shao-Wei Chen; Yu-Ting Tai; Shih-Ming Jung; Fu-Hsiang Ko; Jong-Hwei Su Pang; Pao-Hsien Chu (Food and Chemical Toxicology, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

The effect of dietary lecithin and lipid levels on the growth performance, body composition, hemolymph parameters, immune responses, body texture, and gene expression of juvenile white shrimp (Litopenaeus vannamei) - Chyng-Hwa Liou; Vu-An To; Zhong-Fu Zhang; Yu-Hung Lin (Aquaculture, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Adopting abundant seawater as green chemical activators for preparing high surface area biochar - TsingHai Wang; Yu-Ching Lin; Ci-Jing Hung; Yasi Liao; Ruo-Xin Xu (Bioresource Technology Reports, 2023)

Comparative pulmonary toxicity assessment of tungsten trioxide and tungsten trioxide hydrate nanoparticles - Hsin Her Yu; Yi-Chun Chen; Han-Pang Su; Liliang Chen; Hung-Hsiang Chen; Kun-Yi Andrew Lin; Chia-Hua Lin (Science of The Total Environment, 2023)

Novel fast pesticides extraction (FaPEx) strategy coupled with UHPLC-MS/MS for rapid monitoring of emerging pollutant fipronil and its metabolite in food and environmental samples - Raghavendra Rao Pasupuleti; Yi-Jia Ku; Tseng-Yu Tsai; Hung-Ta Hua; Yu-Chia Lin; Jentaie Shiea; Po-Chin Huang; Gangadhar Andaluri; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Defect inspection of indoor components in buildings using deep learning object detection and augmented reality - Shun-Hsiang Hsu; Ho-Tin Hung; Yu-Qi Lin; Chia-Ming Chang (Earthquake Engineering and Engineering Vibration, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Measuring Heterogeneity in 18F-Fluorodeoxyglucose Positron Emission Tomography Images for Classifying Metastatic and Benign Bone Lesions in Patients with Cervical Cancer - Feng-Yuan Liu; Gigin Lin; Jing-Ren Tseng; Angel Chao; Huei-Jean Huang; Hung-Hsueh Chou; Yu-Chen Chang; Tzu-Chen Yen; Chyong-Huey Lai (Journal of Medical and Biological Engineering, 2021)
Purpose Heterogeneity assessment can be applied for medical imaging analysis. Here, we evaluated first-order and texture analysis (TA) metrics in 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) imaging for classification of metastatic and benign bone lesions in patients with cervical cancer. Methods The data of 18 F-FDG PET studies performed on a specific PET/CT system from 2016 to 2018 in patients with cervical cancer were retrieved. The data of bone lesions extracted from studies over 2016–2017 and 2018 were used as training and validation datasets, respectively. Metastatic bone lesions were identified in each dataset, with an equal number of benign bone lesions selected. Cuboid volume of interest (VOI) consisting of 3 × 3 × 5 reconstructed voxels was applied for first-order metrics, and cubic VOI consisting of smaller voxels with trilinear interpolation of standardized uptake value (SUV) was adopted for TA metrics. First-order metrics included the maximum SUV (SUVmax) of lesions and the mean voxel SUV and its standard deviation (SUVsd), skewness, and kurtosis in VOI. In total, 4464 TA metrics based on 62 texture features were evaluated. Logistic regression was used for classification with area under the receiver operating characteristic curve (AUC) as the performance measure. Results From the training and validation datasets, 98 and 42 metastatic bone lesions were identified, respectively. SUVsd demonstrated higher performance than did SUVmax in both the training (AUC .798 vs .732, P = .001) and validation (AUC .786 vs .684, P < .001) datasets. Top-performing TA metrics demonstrated significantly higher performance in the training dataset, but not in the validation dataset. Conclusion A simple first-order measure of heterogeneity, SUVsd, was found to be superior to SUVmax for the classification of metastatic and benign bone lesions. Multiple hypothesis testing can result in false-positive findings in TA with multiple features and parameters; careful validation is required.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Image Segmentation in 3D Brachytherapy Using Convolutional LSTM - Jui-Hung Chang; Kai-Hsiang Lin; Ti-Hao Wang; Yu-Kai Zhou; Pau-Choo Chung (Journal of Medical and Biological Engineering, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

EndoPil: A Magnetically Actuated Swallowable Capsule for Weight Management: Development and Trials - Phuoc Thien Phan; Anthony Meng Huat Tiong; Muneaki Miyasaka; Lin Cao; Hung Leng Kaan; Khek Yu Ho; Soo Jay Phee (Annals of Biomedical Engineering, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Impacts of the influx of e-waste into Hong Kong after China has tightened up entry regulations - Siyi Lin; Yu Bon Man; Ka Lai Chow; Chunmiao Zheng; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Correction to: Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates Excitotoxicity Involving 14,15-Epoxyeicosatrienoic Acid–Mediated Astrocytic Survival and Plasticity to Preserve Glutamate Homeostasis - Yi-Min Kuo; Pei-Chien Hsu; Chia-Chi Hung; Ya-Yu Hu; Yu-Jie Huang; Yu-Ling Gan; Chun-Hua Lin; Feng-Shiun Shie; Wen-Kuei Chang; Lung-Sen Kao; Mei-Yung Tsou; Yi-Hsuan Lee (Molecular Neurobiology, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Acoustic Emission-Feedback Planar Ultrasound System for Localized Blood–Brain Barrier Opening Monitoring - Chih-Hung Tsai; Ko-Ting Chen; Yu-Xian Lin; Yu-Chien Lin; Wen-Shiang Chen; Claude Inserra; Hao-Li Liu (Journal of Medical and Biological Engineering, 2019)

Development of an Image Processing Module for Autonomous Underwater Vehicles through Integration of Visual Recognition with Stereoscopic Image Reconstruction - Yu-Hsien Lin; Shao-Yu Chen; Chia-Hung Tsou (Journal of Marine Science and Engineering, 2019)
This study investigated the development of visual recognition and stereoscopic imaging technology, applying them to the construction of an image processing system for autonomous underwater vehicles (AUVs). For the proposed visual recognition technology, a Hough transform was combined with an optical flow algorithm to detect the linear features and movement speeds of dynamic images; the proposed stereoscopic imaging technique employed a Harris corner detector to estimate the distance of the target. A physical AUV was constructed with a wide-angle lens camera and a binocular vision device mounted on the bow to provide image input. Subsequently, a simulation environment was established in Simscape Multibody and used to control the post-driver system of the stern, which contained horizontal and vertical rudder planes as well as the propeller. In static testing at National Cheng Kung University, physical targets were placed in a stability water tank; the study compared the analysis results obtained from various brightness and turbidity conditions in out-of-water and underwater environments. Finally, the dynamic testing results were combined with a fuzzy controller to output the real-time responses of the vehicle regarding the angles, rates of the rudder planes, and the propeller revolution speeds at various distances.

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Prediction of annual dengue incidence by hydro-climatic extremes for southern Taiwan - Hsiang-Yu Yuan; Tzai-Hung Wen; Yi-Hung Kung; Hsiao-Hui Tsou; Chun-Hong Chen; Li-Wei Chen; Pei-Sheng Lin (International Journal of Biometeorology, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Herpes zoster and the risks of osteoporosis and fracture: a nationwide cohort study - Shu-Man Lin; Chih-Yung Wang; Ying-Yu Chen; Jen-Hung Wang; Chung-Chao Liang; Huei-Kai Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Effect of different ethanolic concentrations on antioxidant properties and cytoprotective activities of Platostoma palustre Blume - Kuan-Hung Lin; Ming-Chih Shih; Po Wang; Yi-Ping Yu; Chun-Ping Lu (Natural Product Research, 2018)

Nonparametric dynamical model of cardiorespiratory responses at the onset and offset of treadmill exercises - Hairong Yu; Lin Ye; Ganesh R. Naik; Rong Song; Hung T. Nguyen; Steven W. Su (Medical & Biological Engineering & Computing, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

NTF3 Is a Novel Target Gene of the Transcription Factor POU3F2 and Is Required for Neuronal Differentiation - Yi-Mei J. Lin; I-Lun Hsin; H. Sunny Sun; Shankung Lin; Yen-Ling Lai; Hsuan-Ying Chen; Ting-Yu Chen; Ya-Ping Chen; Yi-Ting Shen; Hung-Ming Wu (Molecular Neurobiology, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The complete mitogenome of the winged argonaut Argonauta hians and its phylogenetic relationships in Octopoda - Yu-Wen Chiu; Chih-Wei Chang; Hung-Du Lin; Kang-Ning Shen (Conservation Genetics Resources, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Recent Research Progress on the Antidepressant-like Effect and Neuropharmacological Potential of Gastrodia elata Blume - Yu-En Lin; Kuan-Hung Lu; Lee-Yan Sheen (Current Pharmacology Reports, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Insights into the roles of anammox bacteria in post-treatment of anaerobically-treated sewage - Qian Wang; Giin-Yu Amy Tan; Mohammad Azari; Xiaowu Huang; Martin Denecke; Yujie Men; Jin-Young Jung; Satoshi Okabe; Muhammad Ali; Yu-Tzu Huang; Zhuoying Wu; Wai-hung Lo; et al. (Critical Reviews in Environmental Science and Technology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

IGF1R+ Dental Pulp Stem Cells Enhanced Neuroplasticity in Hypoxia-Ischemia Model - Hsiao-Yu Chiu; Chen-Huan Lin; Chung Y. Hsu; John Yu; Chia-Hung Hsieh; Woei-Cherng Shyu (Molecular Neurobiology, 2017)

Enhancing Immiscible Fluid Displacement in Porous Media by Capillary Pressure Discontinuities - C. A. Chung; Hung-Yu Lin (Transport in Porous Media, 2017)

17β-Estradiol and/or estrogen receptor alpha blocks isoproterenol-induced calcium accumulation and hypertrophy via GSK3β/PP2A/NFAT3/ANP pathway - Peiying Pai; Bharath Kumar Velmurugan; Chia-Hua Kuo; Chung-Yi Yen; Tsung-Jung Ho; Yueh-Min Lin; Yu-Feng Chen; Chao-Hung Lai; Cecilia Hsuan Day; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2017)

IL-28 and IL-29 as protective markers in subject with dengue fever - Chih-Hsing Hung; Chung-Hao Huang; Lin Wang; Chun-Chi Huang; Meng-Chieh Wu; Yi-Ying Chin; Chun-Yu Lin; Ko Chang; Deng-Chyang Wu; Yen-Hsu Chen (Medical Microbiology and Immunology, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Therapeutic potential of pro-angiogenic BPC157 is associated with VEGFR2 activation and up-regulation - Ming-Jer Hsieh; Hsien-Ta Liu; Chao-Nin Wang; Hsiu-Yun Huang; Yuling Lin; Yu-Shien Ko; Jong-Shyan Wang; Vincent Hung-Shu Chang; Jong-Hwei S. Pang (Journal of Molecular Medicine, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Methylation and Esterification of Magnolol for Ameliorating Cutaneous Targeting and Therapeutic Index by Topical Application - Chwan-Fwu Lin; Chi-Feng Hung; Ibrahim A. Aljuffali; Yu-Ling Huang; Wei-Chun Liao; Jia-You Fang (Pharmaceutical Research, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress - Hsin-Hung Lin; Kuan-Hung Lin; Jia-Yu Syu; Shun-Yuan Tang; Hsiao-Feng Lo (Journal of Plant Biochemistry and Biotechnology, 2016)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

Data Perturbation Method Based on Contrast Mapping for Reversible Privacy-preserving Data Mining - Yuan-Hung Kao; Wei-Bin Lee; Tien-Yu Hsu; Chen-Yi Lin; Hui-Fang Tsai; Tung-Shou Chen (Journal of Medical and Biological Engineering, 2015)

Dysfunction Screening in Experimental Arteriovenous Grafts for Hemodialysis Using Fractional-Order Extractor and Color Relation Analysis - Ming-Jui Wu; Wei-Ling Chen; Chung-Dann Kan; Fan-Ming Yu; Su-Chin Wang; Hsiu-Hui Lin; Chia-Hung Lin (Cardiovascular Engineering and Technology, 2015)

Pretreatment with Evans blue, a stimulator of BKCa channels, inhibits compound 48/80-induced shock, systemic inflammation, and mast cell degranulation in the rat - Yaw-Syan Fu; Su-Yu Kuo; Hsuan-Yea Lin; Chun-Lin Chen; Shi-Ying Huang; Zhi-Hong Wen; Kun-Zer Lee; Hung-Tu Huang (Histochemistry and Cell Biology, 2015)

Effects of Polypropylene Carbonate/Poly(d,l-lactic) Acid/Tricalcium Phosphate Elastic Composites on Improving Osteoblast Maturation - Hsu-Wei Fang; Wei-Yu Kao; Pei-I Lin; Guang-Wei Chang; Ya-Jung Hung; Ruei-Ming Chen (Annals of Biomedical Engineering, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Production of Arachidonic and Eicosapentaenoic Acids by the Marine Oomycete Halophytophthora - Ka-Lai Pang; Han-Jia Lin; Hung-Yun Lin; Yu-Fen Huang; Yi-Min Chen (Marine Biotechnology, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Aryl hydrocarbon receptor (AhR) agonists increase airway epithelial matrix metalloproteinase activity - Ming-Ju Tsai; Ya-Lin Hsu; Tsu-Nai Wang; Ling-Yu Wu; Chi-Tun Lien; Chih-Hsing Hung; Po-Lin Kuo; Ming-Shyan Huang (Journal of Molecular Medicine, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Aerosol characteristics of different types of episode - Chung-Yih Kuo; Yan-Ruei Lin; Shih-Yu Chang; Chuan-Yao Lin; Chun-Hung Chou (Environmental Monitoring and Assessment, 2013)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Estrogen stimulates the proliferation of human endometrial cancer cells by stabilizing nucleophosmin/B23 (NPM/B23) - Angel Chao; Chiao-Yun Lin; Chia-Lung Tsai; Swei Hsueh; Ying-Yu Lin; Cheng-Tao Lin; Hung-Hsueh Chou; Tzu-Hao Wang; Chyong-Huey Lai; Hsin-Shih Wang (Journal of Molecular Medicine, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Identification and characterization of an indigo-producing oxygenase involved in indole 3-acetic acid utilization by Acinetobacter baumannii - Guang-Huey Lin; Hao-Ping Chen; Jui-Hsin Huang; Tze-Tze Liu; Tze-Kang Lin; Shih-Jon Wang; Cheng-Hsing Tseng; Hung-Yu Shu (Antonie van Leeuwenhoek, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Factors affecting lipid accumulation by Nannochloropsis oculata in a two-stage cultivation process - Chia-Hung Su; Liang-Jung Chien; James Gomes; Yu-Sheng Lin; Yuan-Kun Yu; Jhang-Song Liou; Rong-Jhih Syu (Journal of Applied Phycology, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

2010 oil spill: trajectory projections based on ensemble drifter analyses - Yu-Lin Chang; Leo Oey; Fang-Hua Xu; Hung-Fu Lu; Ayumi Fujisaki (Ocean Dynamics, 2011)

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

Phylogenetic position of a threatened stag beetle, Lucanus datunensis (Coleoptera: Lucanidae) in Taiwan and implications for conservation - Chung-Ping Lin; Jen-Pan Huang; Yat-Hung Lee; Ming-Yu Chen (Conservation Genetics, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Transferability of rice SSR markers to bamboo - Shu-Yun Chen; Yu-Tsung Lin; Chia-Wei Lin; Wei-Yu Chen; Chih Hung Yang; Hsin-Mei Ku (Euphytica, 2010)

Planning for Implementation of Riparian Buffers in the Feitsui Reservoir Watershed - Chia-Ling Chang; Tsung-Hung Hsu; Yunn-Jiin Wang; Jen-Yang Lin; Shaw L. Yu (Water Resources Management, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

A storm event-based approach to TMDL development - Tsung-Hung Hsu; Jen-Yang Lin; Tsu-Chuan Lee; Harry X. Zhang; Shaw L. Yu (Environmental Monitoring and Assessment, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

The functional haplotype of peptidylarginine deiminase IV (S55G, A82V and A112G) associated with susceptibility to rheumatoid arthritis dominates apoptosis of acute T leukemia Jurkat cells - Hui-Chih Hung; Chien-Yu Lin; Ya-Fan Liao; Pei-Chen Hsu; Gregory J. Tsay; Guang-Yaw Liu (Apoptosis, 2007)

Avian Reovirus activates a novel proapoptotic signal by linking Src to p53 - Lin Ping-Yuan; Liu Hung-Jen; Lai Meng-Jiun; Yu Feng-Ling; Hsu Hsue-Yin; Lee Jeng-Woei; Shih Wen-Ling (Apoptosis, 2006)

A GIS Process for Delimitating Areas Potentially Endangered by Debris Flow - Fan-Chieh Yu; Chien-Yuan Chen; Tien-Chien Chen; Feng-Yi Hung; Sheng-Chi Lin (Natural Hazards, 2006)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

Identifications, Classification, and Evolution of the Vertebrate α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid (AMPA) Receptor Subunit Genes - Yu-Chia Chen; Shieh-Shiuh Kung; Bo-Yuan Chen; Chi-Chang Hung; Chun-Chen Chen; Tzi-Yuan Wang; Yi-Mi Wu; Wei-Hsiang Lin; Chyng-Shyan Tzeng; Wei-Yuan Chow (Journal of Molecular Evolution, 2001)